Exploring the Inter-relationship of depressive and anxiety symptoms associated with suicidal ideation among migrant industrial workers in shenzhen: a network analysis approach - Rongxi Wang; Shangbin Liu; Kechun Zhang; Tian Hu; Xinyi Li; Yuzhong Yan; Ming Li; Huachun Zou; Yong Cai (BMC Public Health)
Abstract Objective Internal migrant workers have been experiencing increasing psychological problems recently. This study investigated the interplay between depressive and anxiety symptoms and their association with suicidal ideation among migrant industrial workers, using a network analysis approach. Method Cross-sectional data from 1792 participants were collected using self-reported scales for depressive and anxiety symptoms in Shenzhen, China. Network analysis was adopted to reveal key symptoms and their connections within the network. Results The detected rates of depressive and anxiety symptoms were 40.3% (95%CI: 38.1%~42.6%) and 29.0% (95% CI: 27%~31.2%), respectively. The reported rate of suicidal ideation was 7.9% (95% CI: 6.7%~9.2%). The top ten strongest edges in the model were observed within depression and anxiety domains. “Being so restless that it is hard to sit still”, “Feeling blue” and “Trouble relaxing” were central to the network, while “Feeling nervous, anxious or on edge” and “Sleep disturbance” acted as bridge symptoms in the network. The strongest direct relation to suicidal ideation was anxiety symptom A2 “Unable to stop or control worrying”. Conclusion Findings highlight the interconnected nature of depressive and anxiety symptoms and how these symptoms related to suicidal ideation, thus providing insights for targeted interventions to improve mental well-being among migrant industrial workers in Shenzhen. Intervention strategies focusing on the most influential symptoms such as “restlessness” and “feeling blue” may yield better effectiveness.